2009
DOI: 10.1073/pnas.0902368106
|View full text |Cite
|
Sign up to set email alerts
|

Specific glycosphingolipids mediate epithelial-to-mesenchymal transition of human and mouse epithelial cell lines

Abstract: Epithelial-to-mesenchymal cell transition (EMT) is a basic process in embryonic development and cancer progression. The present study demonstrates involvement of glycosphingolipids (GSLs) in the EMT process by using normal murine mammary gland NMuMG, human normal bladder HCV29, and human mammary carcinoma MCF7 cells. Treatment of these cells with D-threo-1-(3 ,4 -ethylenedioxy)-phenyl-2-palmitoylamino-3-pyrrolidino-1-propanol (EtDO-P4), the glucosylceramide (GlcCer) synthase inhibitor, which depletes all GSLs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
124
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(134 citation statements)
references
References 44 publications
(51 reference statements)
8
124
2
Order By: Relevance
“…Our previous studies using the mouse mammary epithelial cell line NMuMG demonstrated a functional role of Gg4: Expression of Gg4 was reduced by downregulation of Gg4 synthase gene expression during EMT, and enhancement of Gg4 level inhibited EMT (16,17). In contrast, the present study using EtDO-P4, the inhibitor of GlcCer syn- thase (32), did not show involvement of GSLs in EMT process in prostate epithelial cell lines WPE and PNT1a.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Our previous studies using the mouse mammary epithelial cell line NMuMG demonstrated a functional role of Gg4: Expression of Gg4 was reduced by downregulation of Gg4 synthase gene expression during EMT, and enhancement of Gg4 level inhibited EMT (16,17). In contrast, the present study using EtDO-P4, the inhibitor of GlcCer syn- thase (32), did not show involvement of GSLs in EMT process in prostate epithelial cell lines WPE and PNT1a.…”
Section: Discussioncontrasting
confidence: 79%
“…Our recent studies found a reduction in specific GSLs (Gg4 and/ or GM2) in the EMT process induced by transforming growth factor β (TGF-β) in mouse and human epithelial cells (16). Further studies with mouse epithelial NMuMG cells showed that Gg4 synthase is down-regulated during the EMT process and that EMT induction is inhibited by transfection of Gg4 synthase gene or exogenous addition of Gg4 (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This lectin-GSP circuit may be instrumental in maintaining apical transport in MDCK cells. As Guan et al (40) showed in other epithelial cells, different GSPs play a role in maintaining the epithelial state, and this might be attributed to similar lectin-GSP circuits.…”
Section: Discussionmentioning
confidence: 78%
“…The involvement of glycosylation in the EMT process was unclear, particularly in GSLs. Recently, specific GSLs were found to down-regulate during EMT, and enhanced expression of the GSLs blocked the EMT process (22,23).…”
mentioning
confidence: 99%